Multi-objective Optimization Design of Planetary Cycloidal Reducer Structure with Considering Failure Correlation - Shengyu Zheng; Gang Zhao; Zhengming Xiao; Jialin Tan; Jiawei Liu (Jixie chuandong)
The reliability of the planetary cycloidal reducer directly affects the overall performance and service life of industrial robots，among which the reliability of two-stage drive subcomponents has an important influence on the reliability of the whole planetary cycloidal reducer. Taking a heavy-duty planetary cycloidal reducer as the research object，the reliability mathematical model of each subcomponent is constructed based on the force analysis of two-stage transmission system subcomponents，and the reliability is correlated and coupled by Copula function to construct a system reliability model considering failure correlation； on this basis，a multi-objective optimization model with minimum volume and maximum reliability is constructed，and NSGA-Ⅱ（Non-dominated sorted genetic algorithm-Ⅱ） algorithm is used to solve the model，and it is compared and analyzed with the system reliability model considering the independence assumption. The results show that， after optimization，the volume of the reducer is reduced by 11.27%，and the reliability is improved by 5.29%，and the optimal design method considering failure correlation can effectively improve the reliability of the planetary cycloidal reducer with higher comprehensive performance.